Applying Internet-based Writing Course to Improve the Banyumas Tourism Office Staffâs Ability in Writing English Informative Texts - Adiarti, Dian; S, Mimien Aminah; S, Ika Maratus; H, Raden Pujo; Kholifah, Asrofin Nur (Sebelas Maret University, 2016)
Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Attempts at introducing Indonesian tourism attractions to the world are often hindered by the lack of ability to provide proper information. This problem is apparent in regional tourism offices, like Banyumas Regencyâs, where the personnel are usually not highly trained in English. Therefore, a research was conducted to identify the ability of Banyumas tourism office staff in writing descriptive texts and to investigate whether applying internet-based writing course to the staff can improve the ability. This research is experimental in which a group of Banyumas tourism office staff participated. The group got a treatment, i.e. writing course blended with internet as a medium of writing. Pre-test and post-test were conducted to compare the level of writing ability before and after the experiment. Observations, interviews and questionnaire were also employed to obtain data. The results show that the participantsâ ability in writing descriptive texts before the treatment is average. The common problems found were wrong choice of words, incorrect sentence structures, insufficient topic sentences and poor cohesion and coherence within the paragraphs. Comparison between pre-test and post-test indicated that the writing ability of the respondents increased by 30 % in general. Further analysis to the supporting data revealed that the increase is highly attributed to the use of references on the internet, and higher motivation and awareness in writing and revising drafts as they were publicized on-line.Â